Optimalisasi Media Bisnis Online (E-commerce) dalam Mengakselerasi Penjualan Pasca Pandemi Covid-19 - Ni'mah, Fadhilatun; Awaluddin, Murtiadi; Sijal, Mutakallim (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2022)
This research examines the optimization of online business media (e-commerce). The purpose of this study is to find out the comparison of online business media (e-commerce) between marketplace and social media platforms. The research location is located in Gresik City. Primary data was obtained from a survey questionnaire, while secondary data was obtained from the internet. The results of this study are information on the percentage of e-commerce media usage which is most widely used by buyers to meet the needs of daily life, such as 1) lifestyle, 2) food, 3) groceries, 4) household appliances, 5) needs household consumables, 6) skincare, bodycare and makeup.